ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Rocket Chicken Sukorejo Kendal) - Amalina, RA Nur; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
This research was based a sales decrease Rocket Chicken Sukorejo Kendal in the period 2012-2014. The decline in sales can be formulated that how consumers make purchase decisions to buy fast food amid fenomenan culinary competition is getting tighter. This study aimed to examine the effect of price perception, quality of service, and the location of the fast food purchasing decisions on Rocket Chicken Sukorejo.This study uses accidental sampling and purposive sampling with sample of 100 people from the consumers who make purchases at Rocket Chicken Sukorejo Kendal. The analytical method used is multiple linear regression. The results of a study reported the following regression equation: Y = 0.247 X1Â  + 0.304 X2+ 0.308 X3.Based on statistical data analysis, indicators in this study are valid and reliable. In the classical assumption test, regression models multicoloniarity free, does not occur heteroscedasticity, and the normal distribution. The biggest variable is the variable location of 0.308, whereas the smallest variable is the variable perception of the price of 0.247. Results of the study found that all independent variables are positive and significant effect on the dependent variable.